ASSESSMENT OF DYNAMICS OF INFECTIOUS DISEASE ECOLOGY AND EVALUATION OF HUMAN-MOSQUITO INTERACTIONS IN GWAGWALADA TOWN, FCT-ABUJA. - U.N, GIMBA, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Gwagwalada-FCT climate is suitable for several mosquito species capable of transmittingpathogens to humans. The objective of this research, as a theoretical framework, is to assessknowledge of mosquito-borne disease in Gwagwalada-Abuja, as well as perceptions andpractices of mosquito prevention. Five demographic and socioeconomic variables. Knowledge ofmosquito-borne diseases within the area was generally low, with only few individual correctlyidentifying Malaria as a threat in the area. These results can enhance existing public healthprograms by increasing knowledge, addressing public uncertainty and addressing ways to makerecommended practices more effective with the knowledge of how different aspects are perceivedby the varying groups within the community.